Pragmatic moral realism : a transcendental defense - Pihlström, Sami (Value inquiry book series, 2005)
This book examines the issue of moral realism from a pragmatist point of view, drawing attention to our human practices of ethical evaluation and deliberation. It defends the essentially ungrounded and humanly fundamental place of ethics in our thought and action. Ethics must remain beyond justification and ubiquitous in our human form(s) of life.